Characteristics of donor-specific anti-HLA antibodies and outcome in renal transplant patients treated with a standardized induction regimen - Zecher, Daniel; Bach, Christian; Staudner, Christoph; Boeger, Carsten A.; Bergler, Tobias; Banas, Bernhard; Spriewald, Bernd M. (Nephrology Dialysis Transplantation, 2017)
Pre-transplant donor-specific anti-human leukocyte antigen (HLA) antibodies (DSA) have been associated with antibody-mediated rejection (AMR) and early kidney allograft loss. Uncertainties remain regarding the general applicability of these findings and the optimal induction therapy in DSA-positive patients.Pre-transplant sera from 174 patients receiving a crossmatch-negative kidney transplant were retrospectively analysed for DSA using Luminex technology. DSA with mean-fluorescence intensity (MFI) values above 500 were considered positive. All recipients received basiliximab induction and tacrolimus-based maintenance immunosuppression. DSA were monitored post-transplantation in patients with pre-transplant DSA. Antibody results were correlated with the incidence of rejection and graft loss.In total, 61/174 patients had pre-transplant DSA. We found a strong correlation between the presence of DSA against class I and II HLA and DSA MFI greater than 10 000. Both DSA patterns independently predicted an increased risk of early AMR (odds ratio 4.24 and 4.75, respectively, P < 0.05). The risk for AMR in patients with intermediate MFI (3000-10 000) gradually increased with increasing MFI but group sizes were too small to allow for final conclusions. The risk for AMR was comparable to nonsensitized patients in patients with only class I or II HLA-DSA or MFI below 3000. 5-year allograft survival was lowest in patients with simultaneous presence of class I and II HLA-DSA and MFI above 10 000 (45%) but was comparable between patients with only HLA class I or II or no DSA (90.0, 90.0 and 88.1%, respectively). AMR was the only independent predictor of graft loss. Undetectable DSA 14 days post-transplant predicted excellent long-term outcome.. The favourable outcome in the majority of DSA-positive patients despite non-depleting antibody induction and the poor outcome in patients with class I and II HLA-DSA and high DSA strength call for a differentiated therapeutic approach in this patient population.
EVALuna2:25766